Analysis of Chemical Constituents of Chrysanthemum morifolium Extract and Its Effect on Postprandial Lipid Metabolism in Healthy Adults - Lin Chen; Jihan Sun; Zhengyu Pan; Yifei Lu; Zhaodan Wang; Ligang Yang; Guiju Sun (Molecules, 2023)
Chrysanthemum extract possesses antioxidant potential and carbohydrate and fat digestive enzyme inhibitory in vitro. However, no evidence supporting chrysanthemum in modulation of postprandial lipemia and antioxidant status in humans presently exists. This study was to analyze the composition of Imperial Chrysanthemum (IC) extract and determine the effect on changes in postprandial glycemic and lipemic response and antioxidant status in adults after consumption of a high-fat (HF) meal. UHPLC-MS method was used to analyze the components of two kinds of IC extracts (IC-P/IC-E) and in vitro antioxidant activities were evaluated using 1,1-diphenyl-2-picrylhydraxyl (DPPH), 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and Hydroxyl radical (HR) radical scavenging assays. Following a randomized design, 37 healthy adults (age, 25.2 ± 2.6 years, and BMI, 20.9 ± 1.5 kg/m2) were assigned to two groups that consumed the HF meal, or HF meal supplemented by IC extract. Blood samples were collected at fasting state and then at 0.5, 1, 2, 4, 6 and 8 h after the meal consumption. There were 12 compounds with relative content of more than 1% of the extracts, of which amino acid and derivatives, flavonoids, carboxylic acids and derivatives were the main components. Compared with IC-E, the contents of flavonoids in IC-P increased significantly (p < 0.05), and the cynaroside content exceeded 30%. In addition, IC-P showed strong free radical scavenging activity against DPPH, ABTS and HR radicals. Furthermore, according to repeated–measures ANOVA, significant differences were observed in the maximal changes for postprandial glucose, TG, T-AOC and MDA among the two groups. Postprandial glucose has significant difference between the two groups at 1 h after meal and the level in IC group was significantly lower than that in control group. No significant differences were observed in the incremental area under the curve (iAUC) among the two groups. IC significantly improved the serum antioxidant status, as characterized by increased postprandial serum T-AOC, SOD, GSH and decreased MDA. This finding suggests that IC can be used as a natural ingredient for reducing postprandial lipemia and improving the antioxidant status after consuming a HF meal.